2017
DOI: 10.2298/vetgl170324006s
|View full text |Cite
|
Sign up to set email alerts
|

Estrone, 17β-estradiol and progesterone concentrations in processed milk with different fat contents

Abstract: Introduction. The aim of this study was to determine estrone (E1), 17β-estradiol (E2) and progesterone (P4) concentrations in processed milk with different fat contents and to compare the concentrations of these hormones in commercial ultrahigh temperature (UHT) processed milk and commercial pasteurized milk. Materials and Methods. Commercial milks with different fat contents (UHT 0.5 %, UHT 1.5 %, UHT 3.5 % and pasteurized 3.5 % (10 samples of each type of milk)) were purchased in local stores. E1, E2 and P4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Also, further experiments in animals in which long-term treatment with exogenous hormones and comprehensive endocrinological, toxicological, and human epidemiological studies are needed to confi rm or deny the role of exogenous hormones in human health disorders. [72], and Snoj et al [73] .…”
Section: Hormones In Food Of Animal Origin and Consumers' Healthmentioning
confidence: 96%
“…Also, further experiments in animals in which long-term treatment with exogenous hormones and comprehensive endocrinological, toxicological, and human epidemiological studies are needed to confi rm or deny the role of exogenous hormones in human health disorders. [72], and Snoj et al [73] .…”
Section: Hormones In Food Of Animal Origin and Consumers' Healthmentioning
confidence: 96%
“…Pape-Zambito et al [36] reported that E2 concentration in raw whole milk averaged 1.4 ± 0.2 pg•mL -1 of milk (mean ± SEM) and ranged from non detectable to 22.9 pg•mL -1 of milk. Snoj et al [42] found that mean E2 concentration in UHT 3.5% milk (25.37 ± 1.15 pg•mL -1 ) were significantly higher than in UHT 0.5% milk (19.38 ± 0.79 pg•mL -1 ). In the same study, it was suggested that there were significant positive correlations between hormone concentrations and milk fat content, and that high E2 and P4 concentrations indicated that most of the milk in the examined commercial milks came from pregnant cows.…”
Section: Sample Preparationmentioning
confidence: 98%
“…In another study, the P4 level in milk was determined as 9.81 ng•mL -1 or ng•g -1 (12.57 nmol•L -1 ) [21]. Also, Snoj et al [42] found that mean P4 concentration in UHT 3.5% milk (10.76 ± 0.43 ng•mL -1 ) were significantly higher than in UHT 0.5% milk (7.06 ± 0.26 ng•mL -1 ). In addition, previous studies have shown that P4 is also significantly associated with the percentage of fat in milk (r = 0.98) [20].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Taking into account the nutrition value, benefits and scales of consumption of milk and dairy products, the evaluation of quality and safety of this category of products is crucial (Yukalo et al, 2019а). Dairy products are considered a source of various environmental contaminants such as heavy metals (Kukhtyn et al, 2021), pesticides, antibiotics (Bosma et al, 2020), microorganisms (Kang et al, 2020), steroid hormones (Jiang et al 2018;Snoj et al, 2017), etc. Among them, a certain content of esterogenic hormones in milk and dairy products is considered a physiologically natural process (Jouan et al, 2006;Pu et al, 2019;Wang et al, 2020), because they carry out a number of important functions in the body (synthesis of protein, transmission of signals between receptors, growth, regulation of reproduction) (Malekinejad et al, 2006;Hirpessa et al, 2020;Mo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Esterogenic hormones are synthesized by the glands of internal secretion and partially by the mammary gland (Janowski et al, 2002;Feng et al, 2016) and are removed with urine and milk (Hirpessa et al, 2020). The cow milk contains certain natural esterogenic hormones: 17β-estradiol, 17α-estradiol, estriol and estrone (Domenech et al, 2011;Varriale et al, 2015), of which 17β-estradiol is potentially the strongest (Snoj et al, 2017;Lyu et al, 2022). Furthermore, dairy products can include man-synthesized hormones if they are used as growth stimulators and to increase milk production (Capriotti et al, 2015;Snoj et al, 2017;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%